A influência midiática e o consumo de substâncias psicoativas por parte de crianças e adolescentes e a intervenção pedagógico-teológica como estratégia preventiva - Tribess, Marciano (2014)
The goal of this research is to approach and analyze the influence of the media exerted on children and adolescents related to the experimentation of psychoactive substances and the pedagogic-theological intervention as a preventive strategy. The influence on the human being through mediatic mechanisms which condition the person to an action expected by the conditioner has been studied for a long time. Aldous Huxley in his book Brave New World already dealt with the conditionality of the human being ever since the decade of the 30 s. In later decades, other theoreticians such as Edgar Morin and Guy Debord, analyzed how the human being is conditioned through mass culture and the spectacle society. The reality presented led this research to seek preventive ways of dealing with the conditionality of the human being by the media. For this, we analyze theoreticians such as Paulo Freire and Michel Henry and their discoveries on mediating knowledge and the analysis of the Words of Christ and how these can contribute in the elaboration of pedagogic-theological interventions which interfere in the conditioning process of the television publicity propaganda which conveys the use of psychoactive substances. The results point out that in the space of the Christian community the child as well as the adolescent find conditions to reflect and act with criticalness based on the abstract thought propitiated by a non-alienating content.